Innovative Digital-Based Social Policy Models to Combat Urban Poverty - Afrilia, Ufa Anita; Rasyid, Harun; Sutrisno, Dona Saputra Adji; Handayani, Tri Quari; Hasibuan, Masnilam (GoAcademica Research & Publishing, 2025)
Urban poverty continues to show new complexities along with the development of digital technology and rapid social change. Inequality in access to technology has deepened social disparities and marginalized vulnerable groups in the urban ecosystem. On the other hand, conventional social policies are considered not adaptive enough to respond to the dynamics of the needs of the urban poor. This study aims to formulate an innovative digital-based social policy model to combat urban poverty more effectively. This study uses a qualitative approach with data collection through a literature review of various relevant literature. Data are analyzed in depth to find patterns and relationships between elements that contribute to the formulation of digital social policies. The results of the study show that the use of digital technology has great potential in accelerating data collection, increasing public participation, and encouraging policy transparency. Social policy innovations that integrate technology, data, and cross-sector collaboration have proven to be able to respond to structural challenges in the urban policy system. Therefore, the formulated policy model not only offers a more adaptive approach but also becomes a strategic foundation for realizing social justice amidst digital transformation.